Association Splitting: A randomized controlled trial of a new method to reduce craving among inpatients with alcohol dependence. (30th April 2016) - Schneider, Brooke C.; Moritz, Steffen; Hottenrott, Birgit; Reimer, Jens; Andreou, Christina; Jelinek, Lena
Abstract: Association Splitting, a novel cognitive intervention, was tested in patients with alcohol dependence as an add-on intervention in an initial randomized controlled trial. Preliminary support for Association Splitting has been found in patients with obsessive-compulsive disorder, as well as in an online pilot study of patients with alcohol use disorders. The present variant sought to reduce craving by strengthening neutral associations with alcohol-related stimuli, thus, altering cognitive networks. Eighty-four inpatients with verified diagnoses of alcohol dependence, who were currently undergoing inpatient treatment, were randomly assigned to Association Splitting or Exercise Therapy. Craving was measured at baseline, 4-week follow-up, and six months later with the Obsessive-Compulsive Drinking Scale (primary outcome) and the Alcohol Craving Questionnaire. There was no advantage for Association Splitting after three treatment sessions relative to Exercise Therapy. Among Association Splitting participants, 51.9% endorsed a subjective decline in craving and 88.9% indicated that they would use Association Splitting in the future. Despite high acceptance, an additional benefit of Association Splitting beyond standard inpatient treatment was not found. Given that participants were concurrently undergoing inpatient treatment and Association Splitting has previously shown moderate effects, modification of the study design may improve the potential to detect significant effects in future trials. Highlights: Association Splitting sought to reduce craving by strengthening neutral associations with alcohol-related stimuli. Association Splitting has been successfully tried in patients with OCD and eating disorders. There were no differences in decline in craving between Association Splitting and active control. The ambitious study design may have limited ability to find significant results.